2020
DOI: 10.1038/s41598-020-78941-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct systemic cytokine networks in symptomatic and asymptomatic carotid stenosis

Abstract: Inflammatory processes are crucial in atherosclerosis and atherothrombosis. This study aimed to identify a cytokine-pattern that is associated with plaque-vulnerability or symptomatic state in comprehensively investigated patients with symptomatic (sCS) and asymptomatic carotid stenosis (aCS). Twenty-two patients with sCS and twenty-four patients with aCS undergoing carotid endarterectomy (CEA) were considered. A cytokine-panel was measured in plasma-specimens prior to surgery and at a 90 day follow-up. Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…As reported previously, neither the count of MES per hour [median = 0 (IQR: 1) vs. median = 0 (IQR: 1); p = 0.766] nor the histological sum score [median = 2 (IQR: 2.5) vs. median = 2 (IQR: 2); p = 0.517] differed between the patients with sCS and aCS (11).…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…As reported previously, neither the count of MES per hour [median = 0 (IQR: 1) vs. median = 0 (IQR: 1); p = 0.766] nor the histological sum score [median = 2 (IQR: 2.5) vs. median = 2 (IQR: 2); p = 0.517] differed between the patients with sCS and aCS (11).…”
Section: Resultsmentioning
confidence: 50%
“…In this prospective case-control study, we considered patients with sCS or aCS who have been previously described in a previous work from our group investigating distinct plasma cytokine patterns ( 11 ). The study recruitment took place between July 2017 and June 2018 at the Departments of Neurology and Cardiothoracic-, Transplantation- and Vascular Surgery at Hannover Medical School.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, IL2RB is expressed on T cells and NK cells and transfers IL-2 signals (Fernandez et al, 2019). Moreover, previous studies have revealed that high expression of the IL-2 signal was associated with symptomatic CAS (Stauss et al, 2020). GGH is involved in glutamate removal from folate signals in IPA analysis, and overexpression of GGH can lead to more efflux of folate, which might result in folate deficiency (Wani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, phospholipases are associated with the occurrence of cerebrovascular events in CAS patients with high stroke risk ( Zhang et al, 2021 ). The IL-2 level was significantly higher in symptomatic patients than in asymptomatic CAS patients, indicating the potential predictive value of IL-2 signaling in symptomatic CAS ( Stauss et al, 2020 ). In addition, VEGF is critical in the progression of carotid plaque and intraplaque hemorrhage.…”
Section: Discussionmentioning
confidence: 99%